2012
DOI: 10.3390/molecules171011826
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 11b-HSD1 by Tetracyclic Triterpenoids from Euphorbia kansui

Abstract: The roots of Euphorbia kansui are considered an important traditional folk medicine. In this study the ethanol extracts of E. kansui were investigated. A new tetracyclic triterpenoid, euphane-3β,20-dihydroxy-24-ene, in addition to five known triterpenoids with euphane skeletons were isolated. Their structures were elucidated on the basis of physical and spectral techniques (1D-, 2D-NMR and MS, respectively). Furthermore, these compounds 1–6 exhibited strong inhibitory activity against human 11β-hydroxysteroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Except for the two degrees from two pairs of double bond, the remaining four degrees indicated that compound 2 should be tetracarbocyclic. The structure of 2 resembled that of (24 R )‐eupha‐8,25‐diene‐3 β ,24‐diol, except that the C(24) ( δ (C) 76.6) in (24 R )‐eupha‐8,25‐diene‐3 β ,24‐diol was significantly downfield shifted in 2 ( δ (C) 90.3). The observation indicated that C(24) in 2 should be attached to a stronger electron withdrawing group.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Except for the two degrees from two pairs of double bond, the remaining four degrees indicated that compound 2 should be tetracarbocyclic. The structure of 2 resembled that of (24 R )‐eupha‐8,25‐diene‐3 β ,24‐diol, except that the C(24) ( δ (C) 76.6) in (24 R )‐eupha‐8,25‐diene‐3 β ,24‐diol was significantly downfield shifted in 2 ( δ (C) 90.3). The observation indicated that C(24) in 2 should be attached to a stronger electron withdrawing group.…”
Section: Resultsmentioning
confidence: 78%
“…The H–C(3) was α ‐orientated, which can be confirmed by the cross‐peaks of H–C(3)/H–C(5) and H–C(3)/Me–C(28) in ROESY spectrum ( Figure ). Me–C(21) was assigned to be α ‐orientation due to biosynthetic consideration and the coupling constant of Me–C(21) ( δ (H) 0.86, J = 6.0), similar to those of euphanes in Euphorbia . Thus, 1 was elucidated to be 24,24‐dimethoxy‐25,26,27‐trinoreuphan‐3 β ‐ol.…”
Section: Resultsmentioning
confidence: 97%
“…A decrease in epididymal fat weight after a five-week administration of Euphorbia in mice demonstrated the antiobesity effect of Euphorbia . In a previous study [ 16 ] of ethanol extracts of Euphorbia , a new tetracyclic triterpenoid of Euphorbia and five known triterpenoids with euphane skeletons were shown to be potentially useful in the clinical treatment of diabetes. In this study, Euphorbia showed antihyperglycemic effects on FBG and OGTT of obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been reports of its antitumor [ 11 ] and antiviral role [ 12 , 13 ] as well as its ability to regulate the immune system [ 14 ]. Moreover, recent studies have revealed that Euphorbia has anti-inflammatory [ 15 ], antidiabetic [ 16 ], and antiobesity effects [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang (called kansui ) is an effective and commonly used herbal medicine for the treatment of edema, ascites, and asthma [ 1 ]. Recently, it was found that kansui has pharmacological activities including tumor inhibition [ 2 ], anti-viral effects [ 3 , 4 ], immune system regulation [ 5 ], modulatory effects on IFN-γ [ 6 ], and as a diabetes treatment [ 7 ]. Unfortunately, kansui has highly toxic side effects in the liver and kidney, which restricts its clinical application [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%